A228 CAN SERRATED ADENOMA DETECTION RATE (SADR) BE USED TO EVALUATE THE PERFORMANCE OF CREDENTIALED SCREENING COLONOSCOPISTS IN THE NOVA SCOTIA COLON CANCER PREVENTION PROGRAM?. (15th March 2019) - Miles, M; Kilfoil, E; Walsh, G; MacIntosh, D
Abstract: Background: Quality indicators are used to evaluate the effectiveness of colon cancer screening programs. The most commonly reported quality indicator is the Adenoma Detection Rate (ADR) since increased ADR correlates with reduced risk of colorectal cancer and death. Another quality indicator that is gaining popularity is the Serrated Adenoma Detection Rate (SADR) since serrated adenomas are precursors to colorectal cancer and can easily be missed. The utility of reporting SADR is unclear. Aims: The objectives of the study are to (1) determine the SADR; and (2) investigate the relationship between SADR and APC for all screening endoscopists in the Nova Scotia colon cancer program as a means of quality assurance. Methods: This was a retrospective cross sectional review of a prospectively updated colonoscopy database. The study population was asymptomatic, average risk adults age 50–74 who had a screening colonoscopy after a positive fecal immunochemical test (FIT) from 2016–2017 as part of the Nova Scotia Colon Cancer Prevention Program (NSCCPP). ADR was defined as the number of colonoscopies in which one or more adenomas was removed divided by the total number of colonoscopies performed. SADR was defined in a similar manner using serrated adenomas. Pearson correlation coefficients were used to evaluate the relationship between ADR and SADR. Results: A total of 8379 colonoscopies were performed by 42 endoscopists on FIT positive patients over the study period. The mean number of colonoscopies per endoscopist was 200 (range 51–615). The mean SADR for all endoscopists, those with ADR ≥ 50% and those with ADR ≥ 60% are shown in Table 1. There was a significant positive correlation between ADR and SADR (R=0.52; P<0.001). Conclusions: In the NSCCPP, there was a significant positive correlation between ADR and SADR for screening endoscopists, supporting the use of SADR as a quality indicator. The target SADR for endoscopists screening FIT positive patients needs to be determined. Funding Agencies: None